Better antiretroviral central nervous system penetration is not associated with reduced chronic pain in people living with human immunodeficiency virus - Robbins N. (2017)
© 2016 Bentham Science Publishers. Objective: To determine if better antiretroviral (ARV) central nervous system (CNS) penetration is associated with reduced rates of chronic pain in people living with HIV (PLWH). Background: Chronic pain remains prevalent in PLWH despite widespread ARV use. Mechanisms underlying this prevalence remain unknown, though neuroinflammation from persistent CNS HIV infection and maladaptive plastic changes in the CNS have been implicated. Here we hypothesize that better CNS ARV penetration, measured using the CNS Penetration-Effectiveness (CPE) score, would decrease rates of chronic pain. Methods: We interviewed 254 consecutive adults from an HIV clinic in Chiang Mai, Thailand. We collected data on demographics, HIV history, ARV use, and pain characteristics. Patients were evaluated for depression using a Thai two question Patient Health Questionnaire (PHQ-2). Modified CPE score was calculated using established methods and grouped a priori into “low CPE” (≤7, poor penetration) and “high CPE” (≥8, good penetration). CPE score was compared with chronic pain scores in SPSS using appropriate statistical tests. A relationship between CPE score and a positive depression screen was tested further using multivariable binary logistic models. Results: 245 of 254 subjects were on ARVs. Complete ARV data was available for 235 patients. 137 of these 235 patients (58.3%) had a CPE score ≤7, and 98 (41.7%) had a score ≥8. 49 patients had chronic pain, and 9 had neuropathic pain. Low CPE score was not associated with chronic pain (p=0.64), neuropathic pain (p=0.56), or frequent pain (p=0.80), nor was it associated with the severity of reported “worst pain” or “average pain” in the last 24 hours (p=0.18 and 0.48, respectively). Post-hoc analysis revealed that higher CPE score was a significant independent risk factor for depression measured by a positive PHQ-2 screen [OR (95% CI) = 1.29 (1.04-1.61), p=0.02]. This relationship was mediated primarily by exposure to zidovudine. Conclusion: CPE score is not associated with chronic pain in PLWH. Post-hoc analysis demon strated that CPE score, and zidovudine exposure in particular, predicts a positive depression screen. Given the substantial morbidity associated with chronic pain and mood disorders in PLWH, additional studies to determine preventable and treatable factors are imperative.